UPPER CRETACEOUS-OLIGOCENE TETHYAN AGGLUTINATED BENTHIC FORAMINIFERAL SPECIES OF THE GENUS ARENOBULIMINA - Haidar Salim Anan (Geological Behavior)
The agglutinated test of the genus Arenobulimina has trochospirally enrolled, four or more chambers per whorl, aperture interiomarginal with a simple arch or loop, which has a comprising various species. Seven small Upper Cretaceous-Oligocene benthic foraminiferal species of this agglutinated genus Arenobulimina are common in some Tethyan localities: North Atlantic (USA, Trinidad, Labrador Sea), Europe (Spain, France, Germany, Czech, Poland, Sweden), Northeast Africa (Egypt), and Southwest Asia (Palestine, UAE). These species are: Upper Cretaceous A. americana Cushman, Late Maastrichtian A. beitjebrinensis Anan and A. jerusalemensis Anan, Upper Cretaceous-Paleocene A. truncata (Reuss), Paleocene Arenobulimina aegyptiaca (Said & Kenawy) and Paleocene-Eocene A. dorbignyi (Reuss). One Early Eocene – Early-Oligocene species Arenobulimina kaminskii is believed here to be new species.